The National Early Warning Score: Translation, testing and prediction in a Swedish setting. (December 2016) - Spångfors, Martin; Arvidsson, Lisa; Karlsson, Victoria; Samuelson, Karin
Summary: The National Early Warning Score – NEWS is a "track and trigger" scale designed to assess in-hospital patients' vital signs and detect clinical deterioration. In this study the NEWS was translated into Swedish and its association with the need of intensive care was investigated. A total of 868 patient charts, recorded by the medical emergency team at a university hospital, containing the parameters needed to calculate the NEWS were audited. The NEWS was translated into Swedish and tested for inter-rater reliability with a perfect agreement (weighted κ  = 1.0) among the raters. The median score for patients admitted to the ICU were higher than for those who were not (10 vs. 8, p  < 0.0001). AUROC for discriminating admittance to the ICU was 0.68 (95% CI: 0.622–0.739, p  < 0.0001). A regression analysis showed that lower oxygen saturation and a lower level of consciousness were significantly associated with ICU admission (OR 1.27 [1.06–1.52], p  = 0.01 and OR 1.77 [1.12–2.82], p  = 0.02) and may predict admission to the ICU better than the other parameters. The Swedish translated NEWS seems to have excellent inter-rater reliability and can be used without risk of linguistic misinterpretation. High scores for the parameters oxygen saturation and level of consciousness in the NEWS may predict admission to the ICU.